An unusual case of sarcoidosis presenting as calf pain - Sureja, Nayan Patel; Swain, Meenakshi; Murari, Santhi Bhushan; Ravuri, Power (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Sarcoidosis is a multisystem chronic inflammatory disease predominantly affecting the lungs. Myositis as a presenting manifestation of sarcoidosis is extremely uncommon and seldom reported. Here we report a 20-year-old male who presented with bilateral calf pain for six months. On evaluation magnetic resonance imaging showed features of myositis, and muscle biopsy was suggestive of sarcoidosis with granulomatous vasculitis. Positron emission tomography-computed tomography scan revealed involvement of spleen in addition to the muscles. Patient was managed with corticosteroids and azathioprine, and showed good treatment response.